Egypt and Ethiopia: Linkage and Disconnection - Erlich, Haggai (Jama’a: an Interdisciplinary Journal of Middle East Studies, 1998)
The article analyzes cultural and religious dimensions that have linked two ancient entities - Egypt and Ethiopia. Connected by the Nile River and the strategy of the Red Sea, Ethiopia and Egypt shared the same church while their multifaceted dialogue was affected by a Christian-Islamic dichotomy. The rise of modern nationalism and of revolutionary ideologies influenced both societies. The discussion also examines the modern history of Church relations and their impact on the one hand on Ethiopian state-building, and on the other on the demise of Coptic institutionalized autonomy in Egypt.